2020
DOI: 10.1177/1464420720977549
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation on low-cycle fatigue behavior of GO-NH2-reinforced epoxy adhesive

Abstract: In this study, the effect of adding functionalized aminated graphene oxide up to 0.3 wt% was experimentally investigated on the mechanical properties and fatigue behavior of an epoxy adhesive with intermediate toughness. Accordingly, graphene oxide was prepared by a modified Hummers method and was modified with 3-aminopropyltrimethoxysilane silane agent. Bulk samples were then prepared from neat and reinforced adhesive with different weight amounts of aminated graphene oxide. Dumbbell-shaped samples with a not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…When fatigue loads are combined with different temperatures, this can lead to premature and unexpected failure of the adhesive joint. Some authors studied the effect of temperature on the failure mechanism on joints under fatigue conditions, [33][34][35] concluding that the failure mechanism does not significantly change as a percentage of adhesive and cohesive failure. However, lower temperatures resulted in a flatter fracture surface, while above a specific temperature, cracks started to be evident on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…When fatigue loads are combined with different temperatures, this can lead to premature and unexpected failure of the adhesive joint. Some authors studied the effect of temperature on the failure mechanism on joints under fatigue conditions, [33][34][35] concluding that the failure mechanism does not significantly change as a percentage of adhesive and cohesive failure. However, lower temperatures resulted in a flatter fracture surface, while above a specific temperature, cracks started to be evident on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Their experimental investigations also proved the positive effect of an RGO additive up to 0.25 wt% on the final strength of SLJs, especially at high temperatures near the glass transition temperature (T g ) of the adhesive. 13 Dabbagh et al 14 experimentally demonstrated that adding 0.1wt% and 0.3 wt% of functionalized aminated graphene oxide to an epoxy adhesive improves its mechanical properties as well as the fatigue life. Some investigations have reported a dual effect of the addition of graphene into epoxy resin.…”
Section: Introductionmentioning
confidence: 99%
“…The reinforcement of 4 wt.% Al 2 O 3 nanoparticles to the epoxy increased the failure loads of joints having 20 mm overlap length by about 97%. Dabbag et al 17 investigated the mechanical and fatigue behavior of epoxy adhesive by adding functionalized graphene oxide (GO) into the adhesive. They concluded that optimum functionalized GO nanoplatelets weight percentages were 0.1 wt% and 0.3 wt% for the mechanical properties and the fatigue life, respectively.…”
Section: Introductionmentioning
confidence: 99%